Countdown Manipulatives: Accelerating the Subtraction Proficiency of the Grade Two Pupils - Berry, Rosenda Alicwas (Journal of Basic Education Research, 2025)
Purpose of the study: This study aimed to improve the mastery of subtraction among Grade 2 pupils at Bahong Elementary School through the use of countdown manipulative materials: Take-off Visualization, Improvised Wheel Clock Count, and Sequential Ladder Count. Methodology: The respondents consisted of 32 Grade 2 pupils, and data were gathered using pretest and posttest questionnaires. Descriptive statistics and a t-test were used for data analysis. The results revealed that the pupils' mastery level in subtraction improved significantly after the intervention, with the overall posttest Mean Percentage Score (MPS) reaching 93.81%, which is described as "Closely Approximating Mastery." A paired t-test analysis indicated a significant difference in the learners' performance before and after using the manipulative materials, demonstrating the effectiveness of the intervention. Main Findings: The study found that countdown manipulatives effectively improved Grade 2 pupils’ subtraction skills, with the Improvised wheel clock count being the most preferred due its simplicity. These tools helped bridge learning gaps and enhance mathematical understanding. The findings highlight the value of using intercative and innovative materials to boost learner engagement and performance in mathematics. Novelty/Originality of this study: The originality of this study lies in its innovative use of countdown manipulative materials, Take-off Visualization, Improvised Wheel Clock Count, and Sequential Ladder Count to enhance subtraction mastery among Grade 2 pupils. Unlike traditional teaching methods, these manipulatives provide interactive, visual, and hands-on learning experiences tailored to young learners.